ANSYS implementation of the phase field fracture approach (Fracture and Structural Integrity, 2024)
In this study, we present a new implementation of the phase field fracture approach in the finite element code ANSYS and its numerical background. The framework is general, and is supported by addressing several classical 2D boundary value problems as well as the ductile fracture and 3D surface flaws behaviors of particular interest. The 3D implementation exploits the analogy between the phase field formulations and the magnetic vector potential equation. The influence of the mode mixity and biaxiality loading conditions of the cracked bodies on phase fields is evaluated as a function of the crack length scale parameter, characterising the scale at which damage effects become significant. As a result of the FE calculations of phase field distributions for propagating cracks, the effects of both the fracture mode and the biaxial stress-strain state are determined. The size of the fracture process zone or damaged region is determined across a wide range of cracked body loading conditions. Developed code: https://github.com/Andrey-Fog/ANSYS-USERELEMENT-PHFLD.
Keywords: Phase field fracture; finite element analysis; mixed mode fracture; surface cracks; ANSYS